Zero Waste Lifestyle: Gaya Hidup Ramah Lingkungan di Kalangan Anak Muda di Kota Makassar - Riska Devi; Nurul Ilmi Idrus (Universitas Muslim Maros, 2023)
Increased waste production has an impact on environmental problems. This has attracted social attention these days, through preventive efforts to reduce the amount of waste. One of the efforts in dealing with such a problem is by applying a zero waste lifestyle. While the existing literatures paid more attention to provide an understanding of the importance of protecting the environment and how to deal with it, this article discusses environmentally friendly lifestyle among youth. This qualitative research was conducted in the city of Makassar, South Sulawesi, between August and December 2022. There are ten informants involved in this study who have practiced zero waste lifestyle. They vary according to sex (eight women and two men), age (between 22 and 33 years), and status (three college students, two freelancers, a government employee, a bulk store employee, a public organizing staff of WALHI South Sulawesi, a content writer, and anentrepreneur. This study combined in-depth interview and observation as data our collection methods. The study shows that a zero waste lifestyle is present as a one of the efforts to the environmental problem today, aimed to minimize waste production. There are several reasons why some applies a zero waste lifestyle, namely: knowledge, environmental awareness, and thrifting. The practice of applying zero waste lifestyle is based on the 6R’s of theenvironmental sustainability concept which include rethink, refuse, reduce, reuse, rot, and recycle. But, it is not easy to practice a zero waste lifestyle, there are some obstacles faced by those who practice this kind of lifestyle. These obstacles are unsupportive environment and the assumption that a zero waste lifestyle is complicated and is an expensive way of life. Despite the fact that practicing zero waste lifestyle is not an easy and requires one’s strong commitment to apply, but when this become habit, it may have a considerable impact on oneself and others when everyone thinks the same way.